Congenital lichenoid porokeratosis in a child - Subhra Dhar; Shikhar Ganjoo; Samujjala Deb (Wolters Kluwer Medknow Publications, 2022)
Linear porokeratosis is a rare disease that can be congenital or may occur typically during infancy and childhood. It presents clinically as streaks or plaques of reddish-brown papules along the Blaschko lines. The presence of cornoid lamella is pathognomonic on histopathology. We present the case of a 3-year-old female child with classical lesions over the left upper and lower limbs.